6-Amino-2,4,5-trimethylpyridin-3-ol and 2-amino-4,6-dimethylpyrimidin-5-ol derivatives as selective fibroblast growth factor receptor 4 inhibitors: design, synthesis, molecular docking, and anti-hepatocellular carcinoma efficacy evaluation - Chhabi Lal Chaudhary; Dongchul Lim; Prakash Chaudhary; Diwakar Guragain; Bhuwan Prasad Awasthi; Hee Dong Park; Jung-Ae Kim; Byeong-Seon Jeong (Taylor & Francis Group, 2022)
A novel series of aminotrimethylpyridinol and aminodimethylpyrimidinol derivatives were designed and synthesised for FGFR4 inhibitors. Structure-activity relationship on the FGFR4 inhibitory activity of the new compounds was clearly elucidated by an intensive molecular docking study. Anti-cancer activity of the compounds was evaluated using hepatocellular carcinoma (HCC) cell lines and a chick chorioallantoic membrane (CAM) tumour model. Compound 6O showed FGFR4 inhibitory activity over FGFR1 − 3. Compared to the positive control BLU9931, compound 6O exhibited at least 8 times higher FGFR4 selectivity. Strong anti-proliferative activity of compound 6O was observed against Hep3B, an HCC cell line which was a much more sensitive cell line to BLU9931. In vivo anti-tumour activity of compound 6O against Hep3B-xenografted CAM tumour model was almost similar to BLU9931. Overall, compound 6O, a novel derivative of aminodimethylpyrimidinol, was a selective FGFR4 kinase inhibitor blocking HCC tumour growth.